1997
DOI: 10.1164/ajrccm.155.2.9032175
|View full text |Cite
|
Sign up to set email alerts
|

8-Epi-PGF2alpha induces airflow obstruction and airway plasma exudation in vivo.

Abstract: 8-Epi-prostaglandin F2alpha (8-epi-PGF2alpha) is an F2-isoprostane formed mainly via noncyclooxygenase pathways in vivo. We investigated whether 8-epi-PGF2alpha has any effect on airflow obstruction and plasma exudation in vivo. Airflow obstruction was quantified by measuring lung resistance (RL) in anesthetized and ventilated guinea pigs, and plasma exudation was quantified by the Evans Blue dye method (20 mg/kg intravenously). Intratracheal instillation of 8-epi-PGF2alpha (1 nmol or 10 nmol) caused dose-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 20 publications
1
38
1
2
Order By: Relevance
“…OH [132]. Oxidative stress leads to the oxidation of arachidonic acid and the formation of a new series of prostanoid mediators called isoprostanes, which may exert significant functional effects [133], including bronchoconstriction and plasma exudation [134][135][136].…”
Section: Formationmentioning
confidence: 99%
“…OH [132]. Oxidative stress leads to the oxidation of arachidonic acid and the formation of a new series of prostanoid mediators called isoprostanes, which may exert significant functional effects [133], including bronchoconstriction and plasma exudation [134][135][136].…”
Section: Formationmentioning
confidence: 99%
“…Oxidative stress leads to the oxidation of arachidonic acid and the formation of a new series of prostanoid mediators called isoprostanes, which may exert significant functional effects (Morrow, 2000), including bronchoconstriction and plasma exudation (Kawikova et al, 1996;Okazawa et al, 1997;Janssen, 2001).…”
Section: Mediators Of Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…These mediators are produced after lipoperoxidation without the conventional feedback regulation (Marathe et al, 2000), having potential effects on the pathogenesis of allergies. As some authors observed before, lipoperoxidation exerts deleterious effects in asthma (Wood et al, 2003), such as enhancement of airway hyperresponsiveness (Held & Uhlig, 2000;Talati et al, 2006), smooth muscle constriction (Fukunaga et al, 1993;Kawikova et al, 1996), airway obstruction, plasma exudation (Okazawa et al, 1997) and vascular constriction (Kromer & Tippins, 1996;Möbert et al, 1997). These references related these effects to the lipoperoxidation although these effects are classically known to be due to the activity of some proinflammatory mediators generated physiologically by enzymatic pathways in inflamed tissues.…”
Section: Non-enzymatic Oxidation Of Pufas Can Produce Modified Fatty mentioning
confidence: 92%
“…The iPs are formed by the peroxidation of the PUFA arachidonic acid (Morrow et al, 1990) generally esterified in phospholipids, from which they can be released by phospholipase-mediated hydrolysis (Cracowski et al, 2002;Morrow et al, 1990). Some iPs exert important roles in the asthma pathogenesis, such as bronchiolar (Cracowski et al, 2002) and vascular (Morrow et al, 1990) constriction, alveolar plasma exudation (Okazawa et al, 1997) and airways hyperresponsiveness (Sametz et al, 1999). These effects are related to the prostaglandin-like activity conferred to these oxidized PUFAs by the structural similarity with the prostaglandins.…”
Section: Isoeicosanoids: Isoprostanes Isoleukotriene B4 E Isotromboxmentioning
confidence: 99%